Perlindungan Hak Cipta Lagu pada Kasus Penggunaan Backsound Iklan dalam Perspektif Hukum Positif dan Hukum Islam: Studi Putusan No. 991 K/Pdt.Sus-HKI/2022 - Ayudity, Meisa; Khutub , Muhammad (Tasyri' : Journal of Islamic Law, 2025)
The use of songs as background sound in commercial advertisements often raises legal issues, especially when done without the permission of the creator. Protection of song copyright is important in guaranteeing the economic and moral rights of creators, both according to positive law and from the perspective of Islamic law. This study aims to analyze the decision No. 991 K/Pdt.Sus-HKI/2022 regarding copyright infringement of the song "Physical Freshness Gymnastics 1988" which was used in unauthorized advertising, as well as examine its relevance in the framework of maqāṣid al-sharī'ah, especially the protection of property rights (ḥifẓ al-māl). The method used is a normative juridical approach with qualitative analysis through literature studies of laws and regulations, court decisions, and contemporary fiqh literature. The results of the study show that the judge in the cassation decision has acknowledged the violation of the economic rights of the creator, but did not adequately accommodate immaterial damages. From the perspective of Islamic law, the act of using works without permission is classified as a form of prohibited property rights violation. This study emphasizes the importance of harmonization between positive law and protection principles in Islamic law in order to strengthen a fair and equitable copyright legal system.